Synthesis of micro–mesoporous CPO-27-Mg@KIT-6 composites and their test in CO2 adsorption. (18th February 2020) - Villarroel-Rocha, D.; Godoy, Agustín A.; Toncón-Leal, C.; Villarroel-Rocha, J.; Moreno, M. S.; Bernini, Maria C.; Narda, Griselda E.; Sapag, K.
Abstract : Novel composites were synthesised through a fusion between CPO-27-Mg framework and mesoporous silica KIT-6 and tested in the CO2 adsorption. Abstract : In this work, we present the preparation of hybrid materials constituted by a Metal Organic Framework (type CPO-27-Mg) and a mesoporous silica (type KIT-6) which were successfully assembled through an in situ hydrothermal method. The composites were characterised by powder X-ray diffraction (PXRD), Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), microscopic techniques (SEM and TEM), N2 adsorption–desorption isotherms at 77 K and CO2 adsorption at 273 K; these techniques confirmed the obtaining of hybrid materials and not simple physical mixtures. Finally, the hybrid materials were tested in the CO2 adsorption at different temperatures and from 0–10 bar of pressure, where the exposure to high relative humidity were also monitored. The CPO-27-Mg@KIT-6 (1 : 1) and (2 : 1) composites exhibited interesting values of CO2 adsorption capacity, compared with those reported in the literature. Therefore, this study opens new pathways for designing porous structured MOF-based materials with advanced gas separation performance.